Предмет: Алгебра,
автор: mrrp88395
Функцію задано формулою f(x) = 2x² - 3. Знайдіть f(-1).
Ответы
Автор ответа:
1
f(x) = 2x² - 3
Підставимо замість х -1
f(-1) = 2(-1)² - 3 = 2 - 3 = - 1
Автор ответа:
2
Ответ: -1.
Объяснение:
Функцію задано формулою f(x) = 2x² - 3. Знайдіть f(-1).
при х=-1 f(-1)=2(-1)^2-3=2-3=-1.
Похожие вопросы
Предмет: Математика,
автор: mashaqveen
Предмет: Математика,
автор: antipenkok321
Предмет: Физика,
автор: zemlyanskijr
Предмет: Биология,
автор: zhstupakova
Предмет: География,
автор: Qweydukkk2467